Cinderella Formula: The Romance Begins - Hirmawan Wijanarka (Universitas Sanata Dharma, 2022)
As a type of formula fiction, a romance applies a fixed pattern of plot development, including the ending, which is always a happy one: celebrating the unification of the hero and heroine who previously struggled very hard against all obstacles threatening their mutual love. However, it does not mean that discussing the plot of romances is of no use. On the contrary, it is interesting to see how romance writers can create so many possibilities in the structure of the so-called formulaic plot. This study attempts to observe the benefit of characterization in the creation of these various structures of plot development. For this purpose, this study sets up two objectives. Firstly, the study observes the characterization of the hero and heroine as well as the construction of the plots. Secondly, the study points out the significance of characterization in driving the development of the plots. In the light of Cawelty's (1977) perspectives on literary formula and Radway's (1991) ideas about romance, this study concludes that the choice (i.e., the characterization) of